Perceived Risk: Is it Important For Use Intention in Traditional Markets - Aviani, Irena; Kurniawati; Masnita, Yolanda (Syntax Corporation, 2023)
Digitalization has developed with the existence of non-cash payments after the Covid-19 pandemic by the public. However, this situation is inversely proportional to field conditions in traditional markets. Where classic market conditions seem shabby, muddy and still use cash for payment transactions. Using perception theory explains how consumers respond to unique environmental conditions and situations. How consumers perceive and interpret stimuli depends on characteristics and personality. This study aims to determine the effect of consumers' perceived value from non-cash payments and risk perception of consumer intention with psychological security as an intervening variable in traditional markets; the hypothesis proves that use intention does not support the perceived value variable of cashless payment. The sense of use does not help the perceived risk. The perceived value of cashless payments does not support psychological safety. The perceived risk is supported by psychological safety. The preference for the perceived value of cashless payments favours psychological safety. The perceived value of cashless payments against intent of use does not support psychological safety. Psychological safety mediates and is supported by the perceived risk of using intention. Recommendations that can be proposed in future research are the addition of several variables or factors that can also affect the perception of the value of non-cash payments and the risk perception of consumer intentions in the post-Covid-19 context in Traditional Markets. And this research, as an individual characteristic of belief tendencies, is expected to mediate the impact of perceived value on psychological safety.